Dreams [videorecording (DVD)] - Franco, Michel, 1979-; Chastain, Jessica, 1977-; Hernández, Isaac (Actor); Bell, Marshall, 1942-; Friend, Rupert; Cape, Yves; Travers, Mitchell (Greenwich Entertainment, Kino Lorber, 2026)
Fernando, a young ballet dancer from Mexico, dreams of international recognition and a life in the US. Believing his lover, Jennifer, a socialite and philanthropist, will support him, he leaves everything behind narrowly escaping death in the process. However, his arrival disrupts Jennifer's carefully curated world. She will do anything to protect both their futures and the life she has built.